(untitled) (Zaporizhzhia Historical Review, 2021)
The reasons and the purposes of the policy of ukrainizaition that took place in history of our country in 20th-30th years of 20th century are considered in this article. The author analyzes the opinions of many scholars and gives his own treatment of the problem. He provesthat there was an objective necessary of ukrainizaition for a young Ukrainian society of that time.